Is the type and location of grocery stores a predictor of healthy and unhealthy food availability? A cross‐sectional study. Issue 3 (17th April 2019) - Kemp, Caitlin; Collins, Jorja; Palermo, Claire
Abstract : Aim: To investigate whether geographical location or type of store is associated with differences in healthy and unhealthy food availability in grocery stores. Methods: A cross‐sectional study using the Victorian Healthy Food Basket to measure food availability (44 'healthy' and 10 'unhealthy' items) in a convenience sample of 112 stores in urban and regional Victoria, Australia. Logistic regression analyses assessed whether location (regional, urban), distance from capital city central business district (km) and type of store (chain supermarket, independent supermarket and general store) predicted the number of missing healthy and unhealthy food items. Results: There were 54 chain supermarkets, 43 independent supermarkets and 15 general stores, with 56% of stores located in urban areas and 44% located regionally. The strongest significant predictor of missing items was being a general store, which had greater odds (odds ratio (OR) = 136, 95% confidence interval (CI) = 13–1399) of having missing 'healthy' items and missing 'unhealthy' items (OR = 63, 95% CI = 7–575), compared with chain supermarkets. Independent supermarkets had increased odds of having missing 'healthy' items (OR = 7, 95% CI = 2–22) compared with chain supermarkets. Regional store location was a significant predictor of missing 'healthy' and 'unhealthy' items, compared with urban location (OR = 6, 95% CI = 2–25) and (OR = 7, 95% CI = 2–29), respectively. Conclusions: Store type was a stronger predictor of stores having missing 'healthy' and 'unhealthy' food items than the store distance from a large urban centre. General stores and independent supermarkets may be important settings for interventions to improve availability of healthy food.